C-reactive Protein and Hepcidin in Non-Dialysis Chronic Kidney Disease - Putera, Edward Muliawan; Widodo, Widodo; Mardiana, Nunuk (Institute of Topical Disease Universitas Airlangga, 2020)
Complications such as anemia and its clinical consequences arise as chronic kidney diseases progress,. One renal anemia pathophysiology is a disruption of iron metabolism, regulated by the main iron exporter hormone, hepcidin. Chronic kidney disease patients were constantly in an inflammatory state, represented by an increased in C-reactive protein. This inflammatory state would facilitate the liver to secrete hepcidin, which would subsequently follow a decrease of iron circulation, thus resulting in functional iron deficiency. Both acute phase reactants which used thoroughly as markers in tropical and infectious diseases, had their own roles in chronic kidney disease. The correlation of c-reactive protein and hepcidin in chronic kidney disease patients was still controversial. To analyse the relationship between c-reactive protein and hepcidin in non-dialysis chronic kidney disease patients. We conducted an observational cross-sectional study with 40 non-dialysis chronic kidney disease patients who met the inclusion and exclusion criteria. Patients were enrolled with consecutive sampling and were examined for serum c-reactive protein and hepcidin levels.A total of forty subjects (67.5% male with mean age of 50.23 ± 1.04 years) were eligible for enrolment in this study. The most comorbid factor was hypertension (62.5%). The common stage for chronic kidney disease was stage 3 (40%). The mean hemoglobin value was 10.74 ± 0.36 g/dL, mean blood urea nitrogen was 39.98 ± 29.59 mg/dL, and serum creatinine of 4.12 ± 3.39 mg/dL. Mean serum c-reactive protein levels were 3.52 ± 5.13 mg/l. Mean hepcidin level were 94,03 ± 95,39 ng/ml. Serum C-reactive protein levels correlated positively (r=0.487) and significantly (p-value=0.001) with serum hepcidin value. C-reactive protein and hepcidin was significantly correlated in non-dialysis chronic kidney disease patients.